Fuzzy dstar-lite routing method for energy-efficient heterogeneous wireless sensor networks - Imad S. Alshawi; Abdul-Kareem Y. Abdulla; Asaad A. Alhijaj (Institute of Advanced Engineering and Science, 2020)
Sensor devices, in wireless sensor networks (WSNs), are usually equipped with low-capacity batteries and scattered on areas that cannot be reached in most of the cases to recharge or replace these sensors. The available battery energy in the sensor nodes is barely sufficient to transmit a limited quantity of data packets. In this regard, most of the works are designed aiming at achieving high energy efficiency. Due to multiple-hop data transmission and many to one traffic connection, the Imbalanced energy depletion (IED) is an immanent issue in WSNs. Accordingly, this paper suggests an energy efficient routing protocol called fuzzy dstar-lite to produce an optimal pathway data routing for Heterogeneous WSNs (HWSNs). This protocol can also reuse the product path to keep the energy consumption fairly distributed over the nodes of a network. Interestingly, the proposed protocol is demonstrated to be more efficient in decreasing the transmission delay and balancing power consumption when compared with other protocols, i.e. chessboard clustering (CC), PEGASIS, and LEACH. The comparison also showed the proposed protocol has been increased the network lifetime approximately 15%, 40%, and 50% compare with CC, PEGASIS, and LEACH, respectively.